Case report: Rib chondrosarcoma in a small breed canine patient - Mena P., Renán (2021)
The case of a 12-year-old male Chihuahua canine is described, in which a subaxillary rib mass was detected during a routine checkup. Subsequently, by means of cytology and histopathology, it was characterized as a well-differentiated costal chondrosarcoma and an en bloc tumor excision was performed, comprising the third, fourth and fifth ribs. No additional chemotherapy was applied and periodic controls were carried out after the procedure, with no evidence of recurrence or metastasis.